Econometric VAR analysis of the effect of the foreign exchange reserves on macroeconomic variables in emerging countries: The case of BRIC countries - Borivoje D. Krušković (Journal of Central Banking Theory and Practice, 2023)
This paper analyses the effects of the foreign exchange re-serves accumulation on the key nominal and real macroeconomicvariables (GDP, employment, prices and exchange rates) in BRICcountries (Brazil, Russia, India, China). VAR model was used toempirically examine the effect of accumulation of foreign exchangereserves on macroeconomic variables. The empirical results in thispaper show that after the initial shock of foreign exchange reserves,the exchange rate appreciation occurs, which can be explained by thefact that a higher level of foreign exchange reserves gives investorsand rating agencies a lower risk of the country, which can conse-quently lead to appreciation of the foreign exchange rate. In this way,the price reaction would be neutralized. Consequently, the growth offoreign exchange reserves leads to the growth of economic activitymeasured by GDP growth.
Keywords: E52; E58; F31; C50; 330; foreign exchange reserves; VAR; exchange rate; employment; economic growth; inflation